التحكم الإرادي في بعض الأعراض الفسيولوجية والنفسية المصاحبة للقلق والاكتئاب وأنماط السيادة المخية المنبئ به: دراسة تشخيصية لدى عينة من طلبة الجامعة - إبراهيم، مروة محمد مرسي; يوسف، هبة بهي الدين ربيع; رمضان، إيهاب سيد; سلام، داليا السعيد سيد أحمد (جامعة طنطا - كلية الآداب, 2023)
هدفت الدراسة الحالية للتعرف علي نمط الهيمنة المخية السائد لدي عينة الدراسة، بالإضافة للتعرف إذا كان هناك فروق ذات دلالة إحصائية بين نمط الهيمنة المخية وقدرة الفرد على التحكم الإرادي في الأعراض النفسية والفسيولوجية المصاحبة للقلق والاكتئاب وما إذا كان هناك أيضا هناك فروق ذات دلالة إحصائية بين نوع المشارك (ذكر-أنثى) وقدرة الفرد على التحكم الإرادي في الأعراض النفسية والفسيولوجية المصاحبة للقلق والاكتئاب. تكونت العينة من (١٤٠) طالب وطالبة وكانت العينة الاستطلاعية (٤٠) طالب وطالبة من طلاب كلية الآداب قسم علم النفس للعام الدراسي ۲۰۲۱ -۲۰۲۲. بينما تكونت العينة الأساسية من (۱۰۰) طالب وطالبة تم اختيارهم بشكل عشوائي. تم تطبيق مقياس هيرمان للهيمنة المخية ومقياس بيك للاكتئاب ومقياس تايلور للقلق. وأسفرت النتائج على ما يلي: 1. نمط الهيمنة المخية السائد لدي الطلبة هو النمط الأيسر يليه المتكامل. 2. توجد فروق ذات دلالة إحصائية بين قدرة الفرد على التحكم الإرادي في الأعراض النفسية والفسيولوجية المصاحبة للقلق والاكتئاب (ضغط الدم -معدل ضربات القلب-الصداع النفسي) والنمط الأيسر والمتكامل. ولا توجد فروق ذات دلالة إحصائية قدرة الفرد على التحكم الإرادي للأعراض النفسية والفسيولوجية والنمط الأيمن. The current study aims to identify the pattern of brain dominance prevailing in the study sample, in addition to identifying if there are statistically significant differences between the pattern of brain dominance and the individual's ability to voluntarily control the psychological and physiological symptoms associated with anxiety and depression, and whether there are also statistically significant differences between the type of The participant (male - female) and the individual's ability to voluntarily control the psychological and physiological symptoms associated with anxiety and depression. The sample consisted of (140) male and female ,40 male and female students from the Faculty of Arts, Department of Psychology for the academic year 2021-2022. While the basic sample consisted of 100 male and female students, they were randomly chosen. Hermann scale of brain dominance, a Beck's depression scale and Taylor scale for concern have been applied. The results resulted in the following: 1. The prevailing brain dominance of students is the left style followed by the integrated. 2. There are statistically significant differences between an individual's ability to control the psychological and physiological symptoms associated with anxiety and depression (blood pressure - heart rate - psychological headache) and the left and integrated style. There are no statistically significant differences the individual's ability to control the psychological and physiological symptoms and the right style. 3. There are no statistically significant differences between the type of participant (male - female) and the individual's ability to voluntarily control the psychological and physiological symptoms associated with anxiety and depression. 4. The left dominant pattern explained 20% of the ability to voluntarily control heartbeat, and the integrated dominant pattern explained 19% of the ability to voluntarily control the heartbeat, and the integrated pattern also explained 9% of the ability to control mental headache.
Keywords: الطب النفسي -- البرامج الإرشادية -- أنماط التعلم -- العلاج السلوكي -- الضغط النفسي